Author Correction: Multipurpose silicon photonics signal processor core. Issue 1 (December 2017) - Pérez, Daniel; Gasulla, Ivana; Crudgington, Lee; Thomson, David; Khokhar, Ali; Li, Ke; Cao, Wei; Mashanovich, Goran; Capmany, José
Change History: A correction to this article has been published and is linked from the HTML version of this article.